Mechanical Properties of Porous Structures for Dental Implants: Experimental Study and Computational Homogenization - Jíra, Aleš; Šejnoha, Michal; Krejčí, Tomáš; Vorel, Jan; Řehounek, Luboš; Marseglia, Guido (Materials (Basel, Switzerland), 2021)
A combined experimental and numerical study on titanium porous microstructures intended to interface the bone tissue and the solid homogeneous part of a modern dental implant is presented. A specific class of trabecular geometries is compared to a gyroid structure. Limitations associated with the application of the adopted selective laser melting technology to small microstructures with a pore size of 500 μm are first examined experimentally. The measured effective elastic properties of trabecular structures made of Ti6Al4V material support the computational framework based on homogenization with the difference between the measured and predicted Young's moduli of the Dode Thick structure being less than 5%. In this regard, the extended finite element method is promoted, particularly in light of the complex sheet gyroid studied next. While for plastic material-based structures a close match between experiments and simulations was observed, an order of magnitude difference was encountered for titanium specimens. This calls for further study and we expect to reconcile this inconsistency with the help of computational microtomography.
Keywords: homogenization; X-FEM; dental implant; porous material; selective laser melting; FEM; mechanical properties; titanium trabecular and gyroid structures